2021
DOI: 10.2174/1386207323999200918112538
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nano Tubes: Novel Drug Delivery System in Amelioration of Alzheimer’s Disease

Abstract: Background: Alzheimer’s disease is an irreversible, progressive brain disorder manifested with symptoms like loss of memory (known as dementia), personality changes, loss of cognition, impaired movement, confusion, deteriorated planning and thought process. Neurodegeneration in Alzheimer’s disease is the result of deposition of protein beta-amyloid that forms plaques and another protein called tau, forming tangles that prevent proper functioning of nerve cells in the brain. Methods: The goal of the review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…80 Recently, CNTs have been used for AD treatment through inhibiting amyloid fibrillation, disintegratingamyloid fibrils, and promoting the clearance of amyloid plaques. 81 They possess the ability to absorb various large and small biomolecules on their surface, which further inhibits amyloid fibrilization. 81,82 Besides, it has also been found that CNT could change the lag phase time required for nucleus formation, elongation, and saturation of amyloid fibrils.…”
Section: Nanotechnology Mediated Drug Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…80 Recently, CNTs have been used for AD treatment through inhibiting amyloid fibrillation, disintegratingamyloid fibrils, and promoting the clearance of amyloid plaques. 81 They possess the ability to absorb various large and small biomolecules on their surface, which further inhibits amyloid fibrilization. 81,82 Besides, it has also been found that CNT could change the lag phase time required for nucleus formation, elongation, and saturation of amyloid fibrils.…”
Section: Nanotechnology Mediated Drug Therapymentioning
confidence: 99%
“…81 They possess the ability to absorb various large and small biomolecules on their surface, which further inhibits amyloid fibrilization. 81,82 Besides, it has also been found that CNT could change the lag phase time required for nucleus formation, elongation, and saturation of amyloid fibrils. 82 Therefore, CNT-based drug delivery strategies show potential for future AD treatment.…”
Section: Nanotechnology Mediated Drug Therapymentioning
confidence: 99%
“…Genetic material can be delivered to the nucleus and cells with high efficiency using carbon nanotubes. The few studies on CNTs for AD treatment are still in the early stages and need to be further tested for their ability to cross the BBB ( Garalleh, 2018 ; Mishra et al, 2021 ). However, CNTs can be used as biosensors with high sensitivity and selectivity to detect Aβ in human serum, particularly Aβ42 and Aβ40 peptides ( Chen et al, 2022 ).…”
Section: Types and Properties Of Nanomedicinementioning
confidence: 99%
“…conductivity. 47 On the other hand, the electrode surface can be functionalized for better transducer signals by electro-spun nanofibers or metallic nanoparticles, which create binding sites for the immobilization of biomarkers or recognition elements. 48 Nowadays, we have molecularly imprinted polymer (MIP), which filters out noise and interacts only with the target analyte to enhance the sensor's selectivity.…”
Section: Prospectsmentioning
confidence: 99%